Design of slender reinforced concrete column using Indian design code and Chinese design code (dual project) - Tan, Xesman Zhong Hong (2015)
The purpose of this report is to analyse and evaluate the design method of slender reinforced concrete columns suggested in the Indian Code of practice, IS456: 2000 in comparison with the Eurocode 2, BS EN 1992. To further improve the existing IS 456: 2000 design procedures; this report has included a proposal which attempts to modify the existing additional eccentricity equation. This writer has selected 152 columns that were experimented by past researchers. In this report, all 152 columns will be evaluated in four different aspects, factored and unfactored with IS 456: 2000 and factored and unfactored with BS EN 1992. The unfactored procedure will be used primarily to reveal the fundamental conservativeness of the both design codes while the factored procedure will be used to provide another conservative perspective based on the actual industrial design. The 152 columns have concrete strength, fcu ranged from 16.7N/mm2 to 106.7N/mm2, steel yield strength ranged from 2067N/mm2 to 6257N/mm2, ratio of e/h from 0 to 0.75, normalised area of steel reinforcement percentage from 0.88% to 5.24% and ratio of depth L/h from 14.7 to 50. The 4 parametric studies in this research paper have shown that the column load carrying capacity increases when higher strength concrete and/or higher percentage of steel reinforcement is used. Column with higher L/h ratio tends to have a lower compressive strength. In addition, this lower compressive strength will decrease even further when the column has a low e/h ratio. Last but not least, column with a lower e/h ratio will yield a higher load carrying capacity. From the excel calculations, the results have shown that the average factor of safety of unfactored BS EN 1992 is 21.69% higher than the unfactored IS 456: 2000. When considering the two factored average factor of safety, BS EN 1992 is 16.76% higher than IS 456: 2000. While BS EN 1992 is found to be more conservative than IS 456: 2000 in many ways, IS 456: 2000 has yielded a higher factor of safety ratio when it comes to normal strength column (fcu < 55.24N/mm2).